The Roles of Social Worker During Flood Disaster Management in Dayeuhkolot District Bandung Indonesia - MD Kamrujjaman; Binahayati Rusyidi; Oekan Abdoellah; Nunung Nurwati (Journal of Social Work Education and Practice, 2023)
Social work profession has long been involved with disaster management. In this study tried to discover the roles of the social worker of during flood disaster management of Dayeuhkolot community, Bandung, Indonesia. The study was conducted from 2015 to 2017 in Dayeuhkolot district, Bandung, west java, Indonesia